2018
DOI: 10.1016/j.cub.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Single-Parent Expression Is a General Mechanism Driving Extensive Complementation of Non-syntenic Genes in Maize Hybrids

Abstract: Maize (Zea mays L.) displays an exceptional degree of structural genomic diversity [1, 2]. In addition, variation in gene expression further contributes to the extraordinary phenotypic diversity and plasticity of maize. This study provides a systematic investigation on how distantly related homozygous maize inbred lines affect the transcriptomic plasticity of their highly heterozygous F hybrids. The classical dominance model of heterosis explains the superiority of hybrid plants by the complementation of delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 51 publications
8
54
1
Order By: Relevance
“…These results indicate a vital role of constitutively expressed syntenic genes for the maintenance of basic cellular function. In contrast, we found PAV SPE and non-PAV SPE genes are highly enriched in the non-syntenic gene space and depleted for genes with possible functions from the curated gene set, consistent with previous findings (Swanson-Wagner et al, 2010;Paschold et al, 2014;Marcon et al, 2017;Baldauf et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results indicate a vital role of constitutively expressed syntenic genes for the maintenance of basic cellular function. In contrast, we found PAV SPE and non-PAV SPE genes are highly enriched in the non-syntenic gene space and depleted for genes with possible functions from the curated gene set, consistent with previous findings (Swanson-Wagner et al, 2010;Paschold et al, 2014;Marcon et al, 2017;Baldauf et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study using maize root tissue of different developmental stages it was shown that hybrids consistently expressed more genes than inbred parents in all the investigated triplets (Paschold et al, 2012;Paschold et al, 2014;Baldauf et al, 2018). In this study, this same trend was observed for the vast majority of the root triplets (90%, 43 out of 48) ( Figure 3).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The majority of these genes are evolutionarily young, with the evidence that the majority of them are conserved between maize and its wild progenitor teosinte, but only a small minority were found to be conserved at syntenic locations the genome of Sorghum bicolor a related species which diverged from the lineage leading to maize approximately 12 million years ago (Swigoňová et al, 2004;Sun et al, 2018;Springer et al, 2018). The need for non-homology-based functional annotations is pressing in maize, particularly as there is evidence these new and variably-present genes may be involved in hybrid vigor Baldauf et al, 2016Baldauf et al, , 2018. In this project, we evaluated the potential for using supervised machine learning-based classification algorithms to predict the function of annotated maize genes using purely non-homolog-based predictive variables.…”
Section: Introductionmentioning
confidence: 99%